Peningkatan Kebugaran Jasmani Melalui Modifikasi Permainan Kecil Pada Siswa SMP Paramount School - Jumila Jumila; Ramanata Disurya; Endie Riyoko (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
The problem in this study is whether there is an increase in physical fitness of students of SMP Paramaount School, Palembang City. This type of research is quantitative, using Descriptive mode. The population in this study were active students of SMP Paramount School, totaling 15 students in class VIII. The data collection technique used percentage calculations or commonly called relative frequencies. The average result of the 60-meter running test was 7.87 which is included in the good category. The average result of the hanging body lifting test was 9 times which is included in the sufficient category. The average result of the 60-second lying sitting was 30 times which is included in the good category. The average result of the vertical jump test was 63.2 cm which is included in the good category. The average result of the 1,200-meter running test for 3 minutes 45 seconds which is included in the good category. The overall average level of physical fitness in SMP Paramont School Palembang students was 19 which is included in the TKJI Norm range between Values ​​18 to 21 including the good category